Pancreatic exocrine function in severe human chronic renal failure. Issue 5 (May 1982) - Owyang, C; Miller, L J; DiMagno, E P; Mitchell, J C; Go, V L
Abstract : Patients with chronic renal failure have an abnormal immunoreactive gastrointestinal hormone profile, which is characterised by raised fasting serum concentrations of hormones that have antagonistic effects on exocrine pancreatic function. In addition, in this present study we have found that in renal insufficiency cholecystokinin disappears slowly from the plasma after a constant intravenous infusion of the hormone (p = 0.05 compared with healthy subjects). To evaluate whether the stimulatory or inhibitory hormones have a predominant effect, pancreatic exocrine function under conditions of mannitol perfusion of the duodenum and continuous intravenous cholecystokinin stimulation was studied in eight patients who had severe chronic renal failure and eight age-matched and sex-matched control subjects. Compared with healthy subjects, patients with renal insufficiency had hypersecretion of trypsin in response both to mannitol perfusion of the duodenum and to cholecystokinin stimulation (p less than 0.05). No significant differences in lipase secretion were noted between the patients with renal insufficiency and control subjects. These findings are consistent with the hypothesis that, of the abnormally raised fasting serum concentrations of gastrointestinal hormones found in renal insufficiency, hormones that stimulate rather than inhibit pancreatic exocrine function predominate. Secondly, the dissociation between trypsin and lipase outputs in chronic renal failure may suggest a differential trophic influence of stimulatory hormones – that is, hypercholecystokininaemia – on pancreatic exocrine enzyme secretion.